2008
DOI: 10.1098/rspb.2007.1542
|View full text |Cite
|
Sign up to set email alerts
|

Observational learning in chimpanzees and children studied through ‘ghost’ conditions

Abstract: Emulation has been distinguished from imitation as a form of observational learning because it focuses not on the model's actions but on the action's environmental results. Whether a species emulates, imitates or displays only simpler observational learning is expected to have profound implications for its capacity for cultural transmission. Chimpanzees' observational learning has been suggested to be primarily emulative, but this is an inference largely based upon low fidelity copying in experiments when comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
141
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(150 citation statements)
references
References 24 publications
8
141
1
Order By: Relevance
“…But many other tasks are far more opaque in this respect. Hopper et al (2008Hopper et al ( , 2010 have argued that imitation and emulation tend to be applied strategically, where tasks are opaque and transparent, respectively (see also Acerbi, Tennie & Nunn, 2010). Hopper et al (2010) found that children who saw a human model demonstrate the Pan-pipes task were more successful than those who saw a ghost display, suggesting that imitative learning was very helpful for this cognitively opaque task.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But many other tasks are far more opaque in this respect. Hopper et al (2008Hopper et al ( , 2010 have argued that imitation and emulation tend to be applied strategically, where tasks are opaque and transparent, respectively (see also Acerbi, Tennie & Nunn, 2010). Hopper et al (2010) found that children who saw a human model demonstrate the Pan-pipes task were more successful than those who saw a ghost display, suggesting that imitative learning was very helpful for this cognitively opaque task.…”
Section: Discussionmentioning
confidence: 99%
“…In Hopper et al's (2010) study using the Pan-pipes, children showed a marked tendency to use the method they were shown, whether this was by live demonstration or ghost display. Furthermore, in the simpler sliding door task reported in Hopper et al (2008), children's matching to the ghost displays, in contrast to the chimpanzees', persisted beyond the first trial. Other studies using different tasks reinforce these conclusions.…”
Section: Human Emulative Learningmentioning
confidence: 99%
“…She found 602 that children copied the movement of the door in their first response for both a full 603 demonstration and an enhanced control condition; but across all trials a higher level of 604 matching occurred after the full demonstration compared to the enhanced ghost 605 condition, with the level of matching being similar in both the standard ghost control 606 that did not contain an additional social element and the enhanced ghost control. In 607 contrast to the KW task used in the current study, Hopper et al (2008) used a very 608 simple task illustrated by the fact that six out of eight children who were presented 609 with the task in a no information condition were able to successfully extract the 610 26 reward, a level of success that did not significantly differ to the success of the full 611 demonstration group. Thus it remains unclear whether attempting an enhanced ghost 612 control condition by adding a set of passive hands in the current study's box-and-613 tools-only condition with our more complex task, thus signalling a social aspect to the 614 demonstration but providing no information about how these hands move the tools, 615 would result in more initial copying but less fidelity over trials (as in Hopper et al 616 2008) or whether the greater complexity of the KW would produce different results.…”
mentioning
confidence: 94%
“…Interacting with others enables the agents to share knowledge about objects and events, and to learn new skills, which is targeted in social robotics. While cross-species developmental research has shown that emulation can be found in children [4], infants as young as 18 months [5], and even chimpanzees [4], [6], Initial state:…”
Section: Introductionmentioning
confidence: 99%